Powerful : a Powerless story - Roberts, Lauren, 2002- (Roberts, Lauren, 2002- Powerless trilogy, 2024)
Now alone, Adena learns the streets of Loot by herself and meets a mysterious Elite named Kai Azer who harbors a dangerous ability, but their love is quickly interrupted when Adena becomes Paedyn's seamstress for the Purging Trials.